The Role and Mechanism of Meditation on Physical Health and Well-Being – a literature review - Rutkowska, Marta; Bieńko, Mateusz; Król, Tomasz; Toborek, Michalina; Marchaj, Magdalena; Korta, Karolina; Putra, Anna; Niedziela, Natalia; Margas, Mikołaj (Journal of Education, Health and Sport, 2024)
Introduction: The latest researches concerning the effect of the meditation on the well-being show the increased number of meditation proponents due to its benefits to the mental resilience, stress management and also general health. Meditation is increasingly recognized globally for promoting overall well-being. Purpose: This study investigates impact of meditation on mental and physical well-being. It aims at understanding the mechanisms behind the improvements of health, giving special emphasis on its use as a treatment tool and a prevention measure. State of Knowledge: Meditation is validated in terms of the amount of data proving its positive effects on psychological and physical health. Ranging from stress reduction to immune system modulation, cognitive enhancements, and cardiovascular benefits, meditation turns out to be a wide applicability tool. Mediation perception factors such as cultural and social aspects are contrasted, stressing the important of research on its original Buddhist context. Meditation, due to cultural differences, still is a controversial in many areas, especially in social work. Summary: Meditation is a diverse tool for the promotion of the whole person well-being including stress reduction, immunity modulation, enhancement in cognition and cardiovascular health. It is crucial for building resilience, an important part of preventive and clinical psychology, and the medically oriented stress management. Noticing the role of culture, meditation is a significant aid to the improvement of personal, educator, and healthcare provider well-being. Meditation is a versatile tool that can be integrated into various practices, enhancing the overall well-being and life-coping skills of individuals and professionals alike.